The significant impact of Customer Relations Practices (CRP), Information Technology (IT) and Information Sharing between supply chain partners (IS) on product sales / Arawati Agus, Za’faran Hassan and Sarminah Samad - Samad, Sarminah (Faculty of Business Management, 2008)
This paper examines the relationship between supply chain management programs and sales in manufacturing companies in Malaysia. The study measures senior quality managers’ or production manager’s perception of SCM practices and sales in the industry. This study investigates relationships between supply chain management programs and sales through statistical methods such as Spearman’s correlations, Friedman’s rank test and multiple regression analysis. The findings suggest that SCM programs and implementations especially ‘customer relations practices’ (CRP), ‘technology & information’ (IT) and ‘information sharing between supply chain partners’ (IS) have significant correlations and associations with sales. The result also indicates that ‘High salesgenerated companies’ emphasized more on SCM programs such as ‘Customer Relations Practices’, ‘Technology and Innovation’ and ‘Strategic Supplier Partnership’.